Review of ankle inversion sprain simulators in the biomechanics laboratory - Sophia Chui-Wai Ha; Daniel Tik-Pui Fong; Kai-Ming Chan (Elsevier, 2015)
Ankle inversion ligamentous sprain is one of the most common sports injuries. The most direct way is to investigate real injury incidents, but it is unethical and impossible to replicate on test participants. Simulators including tilt platforms, trapdoors, and fulcrum devices were designed to mimic ankle inversion movements in laboratories. Inversion angle was the only element considered in early designs; however, an ankle sprain is composed of inversion and plantarflexion in clinical observations. Inversion velocity is another parameter that increased the reality of simulation. This review summarised the simulators, and aimed to compare and contrast their features and settings.